2013
DOI: 10.1093/infdis/jit369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Oral Human Papillomavirus Among Young Women in Costa Rica

Abstract: Unlike cutaneous HPV types, alpha mucosal HPV types were uncommon in the oral region and were predominately associated with sexual behavior. Clinical Trials Registration. NCT00128661.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 36 publications
6
52
3
Order By: Relevance
“…This is in contrast with the recent report of a significant association between β-HPV detection and HPVs 16/18 infections at the anal canal among HIV-negative men who have sex with men (24). Similarly, in one study, detection of α-HPVs in the oral cavity significantly increased the odds of β-HPV detection (25). …”
Section: Discussionmentioning
confidence: 89%
“…This is in contrast with the recent report of a significant association between β-HPV detection and HPVs 16/18 infections at the anal canal among HIV-negative men who have sex with men (24). Similarly, in one study, detection of α-HPVs in the oral cavity significantly increased the odds of β-HPV detection (25). …”
Section: Discussionmentioning
confidence: 89%
“…Oral sex has been reported to increase the risk of HPV infection among young men (18 - 24 years) and young women (mean age 21.9 years) [12, 13, 54]. On the other hand, other studies did not find a significant association between that and HPV infection in men or women [20, 22, 23]. These conflicting results may be attributed to the characteristics of the study participants (i.e., sexual activity, sexual behavior, and genital HPV infection status of sexual partner).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including studies of healthy subjects prior to 2009 observed a lower prevalence estimate of oral HPV infection (4.5%, 182 of 4070) [40]. HPV16, which causes the overwhelming majority of HPV-OSCCs in the USA [22,23], is the most common oncogenic oral HPV infection detected [39,40,41], with a prevalence of 1–1.3% [39,40]. …”
Section: Introductionmentioning
confidence: 99%
“…In non-HIV-infected adults, these behaviors include: lifetime and recent number of oral sex partners [5052,56], recent number of rimming partners [50] and lifetime number of any sexual partners [39,52] and vaginal sex partners [41,52]. Oral HPV infection has also been associated with surrogates for increased sexual exposure, including history of anogenital warts [42,51] and HSV-2 seropositivity [53].…”
Section: Introductionmentioning
confidence: 99%